LncRNA KCNQ1OT1 promotes the metastasis of ovarian cancer by increasing the methylation of EIF2B5 promoter - Si-Li He; Ya-Ling Chen; Qi-Hua Chen; Qi Tian; Shui-Jing Yi (Molecular Medicine, 2022)
Highlights 1. LncRNA KCNQ1OT1 is upregulated, while EIF2B5 is downregulated in OC tissues and cells. 2. Knockdown of KCNQ1OT1 represses OC cell proliferation and metastasis. 3. KCNQ1OT1 decreases EIF2B5 expression by recruiting DNA methyltransferases into EIF2B5 promoter, thereby promoting OC progression.